Rola administracji rządowej w zakresie rozwoju CSR w Polsce - Teneta-Skwiercz, Dorota (The Role of the Government Administration within the Development Scope of Corporate Social Responsibility in Poland, 2009)
The experience of a great number of European countries clearly shows that the government administration may have an important and meaningful influence on the process of creating favourable conditions which might promote the idea of Corporate Social Responsibility. In the first part of the article the level of CSR's development in Poland is defined. Moreover, some Polish government's initiatives towards CSR are presented. Further direction of necessary changes within the bounds of public policy which are aimed at accelerating the implementation process of CSR in Poland are pointed out.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 106-115